LIVENESS, MULTIFOCALITY, EAVESDROPPING IN ETHNOMUSICOLOGICAL FIELDWORK RESEARCH AT GHANAIAN FESTIVALS AND ROYAL FUNERALS - Nii-Dortey, Moses (International Library of African Music, 2020)
Ethnomusicological research that involves live, sprawling, multifocal and integrated ceremonies often present liveness-induced challenges that may undermine the authenticity of the research outcomes. )is article describes multifocal and integrated music making performances such as festivals and royal funerals in Ghana and how the vagaries of liveness are largely responsible for nuanced peculiarities which every live musical performance assumes. The article argues in favour of a central role for eavesdropping among informed participating audience members in data gathering efforts as an important strategy for dealing with liveness-induced contingencies in multifocal and integrated performance events.
Keywords: Festivals; Ethics; Performance; Ethnomusicology; Audiences; Liveness; Kplejoo Festival; Ghana; Royal Funeral; Multifocality; Eavesdropping; African Music